Edukasi Pengolahan Makanan pada Ibu Melalui Budaya Lokal untuk Menunjang Tumbuh Kembang Anak di Kecamatan Balocci Kabupaten Pangkep: Edukasi Pengolahan Makanan pada Ibu Melalui Budaya Lokal untuk Menunjang Tumbuh Kembang Anak di Kecamatan Balocci Kabupaten Pangkep - Acha, Muhammad Arsyad; Nasir, Sudirman (STIKes Hang Tuah Pekanbaru, 2026)
Child growth and development are strongly influenced by adequate nutritional intake and proper food processing practices at the household level. In many communities, local cultural practices play an important role in shaping dietary habits and child-feeding behaviors. This community service activity aimed to improve mothers’ knowledge and skills in healthy food processing through a local culture–based educational approach to support child growth and development in Balocci District, Pangkep Regency. The activity was conducted using health education methods integrated with local cultural values, including interactive counseling, demonstrations of nutritious food processing using local ingredients, and participatory discussions. A total of 30 mothers with children participated in the program. Evaluation was carried out using pre-test and post-test questionnaires consisting of ten questions related to child nutrition, healthy food processing, and the utilization of local food resources. The results showed a significant improvement in participants’ knowledge after the intervention. The proportion of participants with good knowledge increased from 20% before the activity to 73% after the education session, while the proportion of low knowledge decreased from 40% to 4%. These findings indicate that culturally based health promotion is effective in enhancing mothers’ understanding and practices related to child nutrition and food preparation. In conclusion, integrating local cultural values into health education can serve as an effective strategy to strengthen community participation and improve maternal capacity in supporting optimal child growth and development. This approach is recommended for wider implementation in community health promotion programs. Abstrak Masalah tumbuh kembang anak masih menjadi perhatian dalam kesehatan masyarakat, terutama yang berkaitan dengan praktik pemberian makanan keluarga. Faktor budaya lokal memiliki peran penting dalam membentuk perilaku pengolahan dan konsumsi makanan pada anak. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan pengetahuan dan keterampilan ibu dalam pengolahan makanan berbasis budaya lokal guna menunjang tumbuh kembang anak di Kecamatan Balocci, Kabupaten Pangkep.Metode yang digunakan adalah edukasi partisipatif melalui penyuluhan, demonstrasi pengolahan makanan lokal bergizi, serta pendampingan praktik memasak sehat. Sasaran kegiatan adalah ibu yang memiliki anak usia balita. Evaluasi dilakukan menggunakan pre-test dan post-test untuk mengukur perubahan pengetahuan peserta.Hasil kegiatan menunjukkan adanya peningkatan pengetahuan ibu mengenai pemilihan bahan pangan lokal, teknik pengolahan makanan sehat, serta pemahaman gizi anak. Pendekatan berbasis budaya lokal terbukti meningkatkan partisipasi dan penerimaan masyarakat terhadap pesan kesehatan. Kegiatan ini menunjukkan bahwa integrasi nilai budaya lokal dalam promosi kesehatan efektif dalam meningkatkan praktik pengolahan makanan keluarga dan berpotensi mendukung optimalisasi tumbuh kembang anak.